Report on communicable diseases (2002)
Focuses on dengue fever, Plasmodium malariae and gastro-enteritis. Presents statistics on diseases of interest in the Caribbean; diseases under international surveillance; and diseases of the expanded programme on immunization.
Keywords: INFECTIOUS DISEASES